Strategie radzenia sobie ze stresem dzieci 8- i 9-letnich - Cywińska, Małgorzata (Studia Edukacyjne, 2020)
Stress is an integral part of our lives. It also applies to our childhood. That is why it is so important to know how children cope with stress (how they learn coping strategies) and to equip them with the skill set to cope constructively with stressful situations throughout life. This article describes strategies for coping with stress that are characteristic for children at the end of early school education. They have been identified in the course of my own research aimed at characterizing child stress and relate to a fragment of research activities aimed at 8- and 9-year-old children. The research established that in some children the developmental process of coping with stress has started: children look for, investigate, and think how to cope with difficulties. In this struggle, however, they focus on people ho could be a source of support for them in coping with stressful situations. Among children’s stress coping strategies, an important role is also played by emotionally focused strategies, which are aimed at reducing negative emotions and arousing positive emotions.